The Role of Sustainability Accounting in Mediating and Moderating the Influence of Digital Competence, ESG Understanding, and Green Accounting on Auditor Performance - Adhi, Daniel Kartika; Paramita, Patricia Dhiana; Wahyuningsih, Panca; Harminingtyas, Rudika (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the relationships among digital competence, ESG understanding, and green accounting with auditor performance, with sustainability accounting serving as both a mediating and a moderating variable. The study involved 140 auditors from Public Accounting Firms (KAP) in Semarang, resulting in a final sample of 125 auditors selected through purposive sampling. Data were analyzed using Path Analysis (including the Sobel Test) and Moderated Regression Analysis (MRA). The results indicate that digital competence, ESG understanding, and green accounting each have a positive and significant impact on sustainability accounting. Furthermore, digital competence, ESG understanding, green accounting, and sustainability accounting each exert a positive and significant effect on auditor performance. Additionally, sustainability accounting mediates as well as strengthens (moderates) the impact of digital competence, ESG understanding, and green accounting on auditor performance.